Karakterisasi Kandungan Gizi dan Potensi Bioaktif Bubur Kacang Hijau sebagai Pangan Tradisional Sumber Protein Nabati dan Energi - Dia Elsa Putri; Ardi Mustakim (MUARA KESEHATAN : Jurnal Ilmiah Ilmu Kesehatan, 2026)
Green bean porridge is one of Indonesia’s traditional foods widely consumed by various segments of society. This food is made from mung beans (Vigna radiata) cooked until soft and served with natural sweeteners such as sugar and coconut milk. In addition to being easily accessible and affordable, green bean porridge is known as a good source of plant-based protein and energy. This article aims to review the nutritional content, characteristics of bioactive compounds, and potential health benefits of green bean porridge based on a literature study. The method used was a literature review of scientific journals and other reliable sources. The results indicate that green bean porridge contains carbohydrates, protein, dietary fiber, vitamins, minerals, and phenolic compounds with potential antioxidant activity. Green bean porridge has the potential to be developed as a nutritious traditional food and a functional food based on natural ingredients